Using dinoprostone vaginal insert for induction of labor: A single institute experience - Jen-Yu Tseng; I-Chia Lin; Wen-Hsun Chang; Chang-Ching Yeh; Huann-Cheng Horng; Peng-Hui Wang (Elsevier, 2020)
Objective: To evaluate the factors associated with the successful induction of labor (IOL) in women treated with dinoprostone slow-released vaginal insert. Material and methods: A retrospective study was conducted between June 2017 and December 2017, enrolling 65 patients who underwent dinoprostone slow-released vaginal insert-induced labor. The correlation between the characteristics of the pregnant women and its success, as well as perinatal complications and adverse outcomes were analyzed. Results: Fifty-three of 65 (81.5%) achieved a successful vaginal delivery. Only multi-parous pregnant women were an independent predictor factor for successful induction after dinoprostone slow-released vaginal insert, since all of them succeeded after this strategy treatment (100%, n = 18), compared to 74.5% (35/47) of successful rate in the nulliparous pregnant women with a statistically significant difference (p = 0.018). There were no adverse events occurred in both mothers and their offspring. Conclusion: Dinoprostone slow-released vaginal insert is a good choice for multiparous pregnant women who need IOL, regardless of which reasons are indicated. For nulliparous women, more studies might be needed to evaluate the effectiveness of PGE2 for IOL.